A comparative study on plant diversity in alder (Alnus subcordata) stands of natural and plantation areas (Biodiversitas Journal of Biological Diversity, 2016)
ezaei-Taleshi SA. 2014. A comparative study on plant diversity in alder (Alnus subcordata) stands of natural and plantation areas. iodiversitas 15: 39-47. Diversity index is the useful criteria for evaluating sustainability of forest ecosystems. Current study carried out in Alder (Alnus subcordata C.A. Meyer) stands that located in north forests of Iran. The aim of the study is express the plant diversity indices and positive role of the trees both natural and plantation forms. Data of Alder trees and associated species were recorded in sample plots which lay down in study area randomly. The abundance, density, percentage of frequency of each species was calculated by standard methods. The results of analysis revealed that, 47 species (21 trees and shrubs species and 26 herbaceous species) were abundant in 80 sample plots both in natural and plantations Alder stands. Whilst the results showed that the number of species in natural area (44 species) was more than plantation stands (37 species). Comparison of species distribution in different physiographical situation showed that some species such as Alnus subcordata, Parrotia persica, Rubus hyrcanus and Prunus sp. recorded in spread rang of physiographic variables as elevation, slopes and aspects. The biodiversity criteria as Shannon H’ and Simpsons D and 1/D indexes showed that they were more in natural stands than plantation areas.